Cultural Models of Nature Primary Food Producers and Climate Change - Bennardo, Giovanni (Routledge Studies in Anthropology, 2019)
Drawing on the ethnographic experience of the contributors, this volume explores the Cultural Models of Nature found in a range of food-producing communities located in climate-change affected areas. These Cultural Models represent specific organizations of the etic categories underlying the concept of Nature (i.e. plants, animals, the physical environment, the weather, humans, and the supernatural). The adoption of a common methodology across the research projects allows the drawing of meaningful cross-cultural comparisons between these communities. The research will be of interest to scholars and policymakers actively involved in research and solution-providing in the climate change arena.